Consumer Electronic Devices Portable: The Effect Moderator Adopter Profile the Purchase of Intent - dos Santos, Washington Romão (2016)
Considering the steady growth seen in recent years of electronic devices as facilitators of business transactions, particularly in the B2C segment, in order to better understand the relationship between perceived value and the actual purchase of a product or service by the consumer, this paper presents the results of a study that explores the profile of innovation adopters as possible moderator in the relationship between Perceived Value and Purchase Intention of portable electronics (smartphones, tablets, ultrabooks and readers of e-books). This is a quantitative survey with a sample of 350 respondents collected by snowball sampling on Facebook and later assessed by structural equation modeling (SEM). The results confirm the relationship of Perceived Value in Purchase Intent as well as sustain the moderating influence of the adopter's profile on this relationship. Among the antecedent variables related to the adoption of technology, it is noteworthy that the Perceived Ease of Use, Perceived Complexity and Risk Perceived no significant effect on the Perceived Value. Finally, the survey results indicate that organizations should seek to develop actions according to the different consumer profiles.